Combination Effect of The Extract of Avocado Leaf and Seed (Persea americana) on Level of Total Cholesterol, LDL, and HDL in Mice (Mus musculus) with Hypercholesterolemia - Muhammad Rafif Alfian Dita; Indri Safitri Mukono; Maftuchah Rochmanti (Biomolecular and Health Science Journal, 2019)
Introduction: Traditional and herbal medicine are two of the primary treatments in a developing country. Both avocado leaf extract and avocado seed extract (Persea americana) have been proven to have an antihyperlipidemic effect in experimental animals. This study was conducted to analyze the effect of avocado leaf and seed extract in a combination form on total cholesterol, LDL, and HDL of hypercholesterolemia mice induced by high fat diet and duck egg yolk.Methods: The sample unit of this study consisted of 25 mice (Mus musculus) and divided into 5 groups: KO1 (control), KO2 (hypercholesterolemia group), KO3 (1st treatment group), KO4 (2nd treatment group), and KO5 (3rd treatment group). The induction phase was done for 35 days, whilst the treatment phase was done for 28 days. All data were analyzed using t test and one-way ANOVA.Results: Administration of the combination including avocado leaf and seed extract (CALSE) in all treatment group proved to decrease total cholesterol and LDL level in mice although it was not statistically significant (p=0,420; p=0,882). Meanwhile, CALSE had a different effect on HDL KO3 level with HDL KO4 and KO5 level, in which HDL KO3 level tended to decrease and HDL KO4 and KO5 level tended to increase.Conclusion: In conclusion, CALSE has the potential to act as an antihyperlipidemic agent which derive from flavonoid and saponin. The potential efficacy might be achieved in a combination rather than in an individual form.